Self-Guided Study Module for Thoracic Radiological Anatomy - Andrew Warejko Phillips; David Charles Binder; Mylene H. Remo; Callum F. Ross; Christopher Straus (Association of American Medical Colleges, 2012)
Abstract Appreciation of thoracic anatomy spatial relationships is critical for long-term comprehension of anatomy. This self-guided study module for thoracic anatomy highlights important structures and guides students at their own pace through the complex process of realizing spatial relationships viewed in radiology atlases of serial and still imaging. The module is intended to be used in conjunction with a human gross anatomy course to create synergistic learning of anatomy by multiple representations of structures. The guide makes complex radiological atlases, which often contain overwhelming numbers of labels and descriptions, more accessible to students. The descriptions in the guide are intentionally compatible with any serial imaging radiological atlas of normal thoracic human anatomy, digital or print. In addition, included in this guide are extensive single-frame images and labeled serial imaging, which may be of use to instructors and students as a stand-alone resource in and of themselves. This study guide has been time-tested for 4 years, with improvements each year. These materials were successfully implemented in 2008 and 2009, revised based on student feedback and study outcomes, and reimplemented in 2010 and 2011. Included here are the 2011 materials. Strongly positive student feedback was received, and formal evaluation of the 2008 version demonstrated statistically and practically significant higher radiology and gross anatomy exam scores (approximately a letter grade) when students utilized the study guide.